The Impact of Dialogue in Achieving Religious Coexistence: The Migration to Abyssinia as a Model - Alsmadi, Abdalrahman Ahmad Kayed (Journal of Ecohumanism, 2025)
This paper addresses one of the most important issues in religious and human studies today: the issue of coexistence among followers of different religions. This is particularly relevant in these times when borders have dissolved, societies have opened up to one another, and an individual’s interaction with those who differ in belief and religion has become an almost daily occurrence. While the Western call for coexistence represents an exceptional initiative and an attempt to solve problems that humanity has fallen into and whose consequences all societies, East and West, have experienced, the principle of coexistence is considered an authentic principle of Islam, indeed part of its creed. Since this is the case, Muslims today must fulfill their duty in this field. This paper constitutes an attempt to establish the theoretical foundation for the principle of coexistence among followers of different religions and the impact of dialogue in achieving it, relying on the study of dialogues that took place before and during the presence of Muslims in Abyssinia after the Prophet (peace be upon him) directed his followers to migrate there and live in a society that embraced a religion different from theirs. The result was the achievement of coexistence in an atmosphere of understanding and harmony.